Recurrent Lower Respiratory Tract Infection in a Renal Allograft Recipient: A Rare Case of Tracheobronchomegaly (Mounier-Kuhn Syndrome) - Monideep Saha; Deepak Panigrahi; Dinesh Khullar; Kulwant Singh; Abhishek Singh; Ajay Lall (Indian Journal of Transplantation)
Mounier-Kuhn syndrome (MKS), also known as tracheobronchomegaly (TBM), is a rare disorder characterized by marked dilatation of the trachea and proximal bronchi. We hereby present a case of MKS in a 40-year-old renal transplant recipient. He had multiple admissions in the recent past for lower respiratory tract infections. During recent admission for lobar pneumonia, he continued to exhibit respiratory symptoms including cough and fever, despite culture-sensitive antibiotics. Imaging studies revealed tracheal and bronchial dilatation with right lower lobe consolidation. Bronchoscopy confirmed TBM and severe excessive dynamic airway collapse. Mucolytics, chest physiotherapy, and intermittent continuous positive airway pressure were game changers in this case. This case highlights the importance of recognizing structural lung pathology in solid organ transplant recipients presenting with recurrent respiratory tract infections.